Trimodal therapy in squamous cell carcinoma of the esophagus - Matuschek, C (BioMed Central, 2011)
Patients with ESCC (squamous cell carcinoma of the esophagus) are most commonly diagnosed with locally advanced tumor stages. Early metastatic disease and late diagnosis are common reasons responsible for this tumor's poor clinical outcome. The prognosis of esophageal cancer is very poor because patients usually do not have symptoms in early disease stages. Squamous cell carcinoma of the esophagus frequently complicates patients with multiple co-morbidities and these patients often require interdisciplinary diagnosis and treatment procedures. At present time, neoadjuvant radiation therapy and chemotherapy followed by surgery are regarded as the international standard of care. Meta-analyses have confirmed that this approach provides the patient with better local tumor control and an increased overall survival rate. It is recommended that patients with positive tumor response to neoadjuvant therapy and who are poor surgical candidates should consider definitive radiochemotherapy without surgery as a treatment option. In future, EGFR antibodies may also be administered to patients during therapy to improve the current treatment effectiveness. Positron-emission tomography proves to be an early response-imaging tool used to evaluate the effect of the neoadjuvant therapy and could be used as a predictive factor for the survival rate in ESCC. The percentage proportions of residual tumor cells in the histopathological analyses represent a gold standard for evaluating the response rate to radiochemotherapy. In the future, early response evaluation and molecular biological tests could be important diagnostic tools in influencing the treatment decisions of ESCC patients.